Talleres para docentes: actividades para la atención de la diversidad escolar - Fontana Hernández, Angélica (Revista Electrónica Educare, 2007)
The attention of all students represents a big challenge for the Costa Rican educational system and all significant required transformations are pushed since its foundationsThe school, understood as a social institution, space in which diversity is approached and also responsible for the instruction of future generations, is facing the difficult task of providing appropriate answer to the diverse needs of the student population.From this perspective, a proposal is designed in order that allows teachers from General Basic Education (pree-school, I and II cycles, special and foreign language classes) to develop skills in the implementation of pedagogic strategies for the attention of classroom diversity.The proposal includes ten workshops that follow a reflection-participation-construction and exchange process. Participants will be able to express their ideas, interests and emotions concerning the topics discussed. They will also develop concepts, materials and didactic strategies for the attention of their students.